A ecopoética de Carlos Drummond de Andrade e Rolf Jacobsen: formulações sobre o antropoceno na lírica moderna - Matheus Saez Magalhães e Silva (2023)
This dissertation aimed to investigate how ecological transformation is represented as a historical process in the works of Rolf Jacobsen and Carlos Drummond de Andrade. To achieve this general objective, the support that ecocriticism can offer for a materialist analysis of modern poetry was explored; the historical relationship of these poets with environmentalism was studied; and the role of particularities and universality in the authors' works as ecopoetic formulation was investigated. The first chapter investigated the ecological topos in literary tradition, divided into three sections. The first explores the concept of Anthropocene and its relevance to literature, as well as the contradictions present in its formulation. The second section delves into the modernist literary tradition with ecopoetics, emphasizing the intersection between literature and ecology through ecocriticism. The last section addresses the political issues that permeated the authors' lives and how this influenced their conception of reality and the effect on their works. The second chapter is divided into a preamble and two parts in which the authors' poems are analyzed from the perspective of time and space, respectively. This dissertation sought to contribute to the understanding of modern poetry as a form of reflection on environmental issues and demonstrate how poetry captures the temporal, socio-spatial, and economic changes that occur in contemporary society, as well as the catastrophes arising from these changes. Through the translation and analysis of the works of Rolf Jacobsen and Carlos Drummond de Andrade, this dissertation offers reflections on the relationship between literature and ecology as a critique of capitalism and seeks to ground these analyses from a materialist and engaged perspective.